2016
DOI: 10.1177/0898010115605231
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Social Determinants, Social Capital, and Health Expertise on Health and the Rural Church

Abstract: In rural communities, religious places can significantly shape health for individuals, families, and communities. Rural churches are prominent community centers in rural communities and are deeply woven into rural culture. Thus, health influences arising from the rural church likely have health implications for the greater community. This article explores health influences emerging from rural churches using social determinants of health, social capital, and health expertise. Although nurses are important healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The third participant was the pastor of a local church who was recruited via his administrative assistant with whom the first author met early on during recruitment efforts. The diversity of ways in which participants were recruited via church-based gatekeepers supports the notion that churches maintain a unique cultural and institutional space in rural communities (Plunkett, Leipert, & Olson, 2016). Furthermore, a review of rural definitions of health found that many rural dwellers define health in terms of their ability to attend church and church activities (Gessert et al, 2015).…”
Section: Discussionmentioning
confidence: 71%
“…The third participant was the pastor of a local church who was recruited via his administrative assistant with whom the first author met early on during recruitment efforts. The diversity of ways in which participants were recruited via church-based gatekeepers supports the notion that churches maintain a unique cultural and institutional space in rural communities (Plunkett, Leipert, & Olson, 2016). Furthermore, a review of rural definitions of health found that many rural dwellers define health in terms of their ability to attend church and church activities (Gessert et al, 2015).…”
Section: Discussionmentioning
confidence: 71%
“…Working in concert, hospitals, churches, not for profits, and academic institutions can use the community health needs assessments, often done by faith-based not-for-profit health systems, as a road map for strategic planning. This alignment in population health strategies results in the betterment of the communities that overlap each entity's service area (Levin 2013;Plunkett et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the Catholic and Mormon churches are more likely to embody hegemonic Christianity than smaller churches in town. Building on Plunkett et al (2016), variability between churches and church cultures can shape whether hegemony takes hold and the extent to which it impacts vulnerable people, indicating that hegemonic Christianity is a product of traditional religious underpinnings rather than a deterministic force that pervades all church institutions. We organize our analysis according to the ecological model below (see Figure 1).…”
Section: Findings: the Social Ecology Of Rural Churches And Religionmentioning
confidence: 99%
“…With this power comes great influence, particularly in rural communities where many rely on religious and spiritual institutions for guidance, counsel, and resources such as food and clothing (Bouchard, Price, and Swan 2020). Rural Christian churches possess concentrated social capital, as they create and maintain community relationships and are important resource‐providers for those in poverty and those experiencing housing and food insecurity (Bartkowski and Grettenberger 2018; De Marco, Thorburn, and Kue 2009; Garland 1988; Plunkett, Leipert, and Olson 2016).…”
Section: Introductionmentioning
confidence: 99%